2018
DOI: 10.1111/bjet.12624
|View full text |Cite
|
Sign up to set email alerts
|

The effects of mind games in math and grammar courses on the achievements and perceived problem‐solving skills of secondary school students

Abstract: The goal of this study is to determine the effectiveness of mind games played by secondary school sixth grade students as classroom activities in math and grammar courses on their perceived problem-solving skills and achievements. In the quantitative part of the study, the nonequivalent groups pre-test-post-test control group design from single-factor quasi experimental designs was used. Qualitative data collection and analysis approaches have also been used to support and explain quantitative data. The study'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…In this respect, it is thought that this study on Turkish vocabulary teaching to refugee students will contribute to the field. In addition, the literature provided few studies on intelligence games (Altun, 2019;Baki, 2018;Bas, Kuzu and Gok, 2020;Bottino, Ott and Benigno, 2009;Bottino, Ott and Tavella, 2013;Cagır, 2020;Demirel, 2015;Demirel and Karakus Yilmaz;Fiangga 2014;Lin, Shao, Wong, Li and Niramitranon, 2011;Sadikoglu, 2017). However, although there are findings that intelligence games improve linguistic skills, when these studies are examined, no studies on vocabulary teaching have been found.…”
Section: Introductionmentioning
confidence: 99%
“…In this respect, it is thought that this study on Turkish vocabulary teaching to refugee students will contribute to the field. In addition, the literature provided few studies on intelligence games (Altun, 2019;Baki, 2018;Bas, Kuzu and Gok, 2020;Bottino, Ott and Benigno, 2009;Bottino, Ott and Tavella, 2013;Cagır, 2020;Demirel, 2015;Demirel and Karakus Yilmaz;Fiangga 2014;Lin, Shao, Wong, Li and Niramitranon, 2011;Sadikoglu, 2017). However, although there are findings that intelligence games improve linguistic skills, when these studies are examined, no studies on vocabulary teaching have been found.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, it is believed that giving individual feedback to the students regarding their concept maps and problem solving on the Google Classroom has a positive effect on their problem solving skills. In support of this finding, Demirel and Karakus Yilmaz emphasized in their studies that feedback and activities were important factors in improving the students' problem solving skills [61].…”
Section: Discussionmentioning
confidence: 82%
“…When the students' views were asked in addition to the teacher, the students expressed positive effects of the games on them. Unlike the teachers, the students reported that their academic success increased and they socialized with intelligence game activities (Demirel & Yilmaz, 2019). They reported that the mind and intelligence games would contribute to relating, reasoning, mathematical communication and problem-solving skills (Cetin & Ozbugutu, 2020).…”
Section: Discussionmentioning
confidence: 99%